Pola Musiman Kunjungan Wisatawan Mancanegara Ke Bali - Maulana, Addin; Koesfardani, Chamma Fitri Putri Pradjwalita (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
The seasonal pattern of tourist arrivals is an important element that must be observed in making policies in the field of tourism marketing. By using the method of calculation, the Seasonality Ratio, Gini Coefficients, and Seasonality Index, this study aims to identify seasonal patterns of foreign tourist arrivals to Bali during the past 5 years. This study shows that: First, foreign tourists’ arrivals to Bali showed insignificant levels of variation and an equation of seasonal variations patterns is found in 2015, 2016, and 2019. Second, foreign tourist arrivals to Bali had a distribution per month that is relatively evenly distributed, with low seasonal rates, or the difference between monthly arrivals has an insignificant difference in value. Third, peak season of foreign tourists’ arrivals to Bali was concentrated in July with a drastic increase from the previous month and accompanied by a slowing decline towards the off-peak season. So, it is necessary to do an appropriate marketing and resource allocation strategies to optimize each seasonal phase.